Effect of different head position during tracheal intubation on postoperative sore throat: a randomized clinical trial - Tao Shan; Huimin Zhang; Xiao Zhou; Hongguang Bao; Liu Han; Chuan Su; Qilian Tan; Jun Yin; Tao Dan (Annals of Medicine)
Introduction Postoperative sore throat is the most frequently complaint after tracheal intubation. We aimed to determine whether changing patients’ head position during intubation reduces the incidence of postoperative sore throat.Methods We randomized 130 patients receiving oral tracheal intubation into one of the two groups: the sniffing position group and elevation position group. Patients in the sniffing position group maintained sniffing position consistently during intubation, while those in the elevation position group transitioned from the sniffing position to the elevation position during tube advancement to the trachea. The primary outcome was incidence of airway trauma and postoperative sore throat (none/mild/moderate/severe) 1 h after surgery. The secondary outcomes were the incidence of postoperative sore throat at 6 h,12 h and 24 h, and hoarseness at 1 h, 6 h,12 h and 24 h postoperatively.Results One hundred twenty-eight patients completed our trial. There were no differences in the baseline characteristics of the patients between the sniffing position and elevation position group [51 (14.8) vs 53 (15.5) for age, 25/39 vs 26/38 for sex (male/female)]. No difference in basic airway condition was observed. Transitioning patient’s head from sniffing to elevation position during tube advancement to tracheal resulted in a significantly lower incidence of airway trauma [10/64 vs 23/64, risk ratio (95% CI): 0.76 (0.61–0.94), p = 0.009], postoperative sore throat and hoarseness compared with maintaining the sniffing position at 1 h [10/64 vs 30/64, risk ratio (95% CI): 0.63 (0.49–0.81), p < 0.001 for sore throat; 22/64 vs 34/64, risk ratio (95% CI): 0.71 (0.52–0.98), p = 0.044 for hoarseness] and 6 h [4/64 vs 17/64, risk ratio (95% CI): 0.78 (0.67–0.92), p = 0.006 for sore throat; 12/64 vs 27/64, risk ratio (95% CI): 0.71 (0.56–0.91), p = 0.002 for hoarseness]. There were no significant differences in postoperative sore throat and hoarseness at 12 and 24 h between the two groups.Conclusions Transitioning patients’ head position from the sniffing position to a head elevation position during tube advancement into tracheal could significantly reduce the incidence of airway trauma, postoperative sore throat and hoarseness.Trial registration number ChiCTR2300073198